Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29 million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 : 103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Casual Empire: Video Games as Neocolonial Praxis - Harrer, Sabine (Open Library of Humanities, 2018)
As a media form entwined in the U.S. military-industrial complex, video games continue to celebrate imperialist imagery and Western-centric narratives of the great white explorer (Breger, 2008; Dyer-Witheford & de Peuter, 2009; Geyser & Tshalabala, 2011; Mukherjee, 2016). While much ink has been spilt on the detrimental effects of colonial imagery on those it objectifies and dehumanises, the question is why these games still get made, and what mechanisms are at work in the enjoyment of empire-themed play experiences. To explore this question, this article develops the concept of ‘casual empire’, suggesting that the wish to play games as a casual pastime expedites the incidental circulation of imperialist ideology. Three examples – Resident Evil V (2009), The Conquest: Colonization (2015) and Playing History: Slave Trade (2013) – are used to demonstrate the production and consumption of casual empire across multiple platforms, genres and player bases. Following a brief contextualisation of postcolonial (game) studies, this article addresses casual design, by which I understand game designers’ casual reproduction of inferential racism (Hall, 1995) for the sake of entertainment. I then look at casual play, and players’ attitudes to games as rational commodities continuing a history of commodity racism (McClintock, 1995). Finally, the article investigates the casual involvement of formalist game studies in the construction of imperial values. These three dimensions of the casual – design, play and academia – make up the three pillars of the casual empire that must be challenged to undermine video games’ neocolonialist praxis.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé